Neko Cat Hotel / Ammar Asyraf Azlan ... [et al.] - Azlan, Ammar Asyraf; Mazilan, Azrul Hazim; Ahmad Nizam, Dania Arrisya; Iberahim, Nur Azira; Yusaini, Nur Hazirah (2023)
Neko Cat Hotel offers boarding and nursing services for animals when their owners are unable to take care for them. Our goal is to provide excellent service while also introducing pets to a new environment situation. We’ll make sure our services are well-liked by the clients. Our goal is to establish ourselves as Malaysia’s premier all-inclusive services which is hotel for cat services, pet essential care and pet essential products. Since our firm is a startup, we must take into account all factors to ensure that we can sustain our operations, particularly financially so that we can compete with other cat hotels. The modal for our Neko Cat Hotel is RM500000 for all the things to establish this cat hotel. As we can see, nowadays a lot of people have cat as their pets at home. However, there are occasions when some pet owners may have to leave their animal at home alone because they are too busy or want to take a long vacation. We see this as an opportunity to increase our customer base in addition to easing the owner’s workload so they may continue with their regular duties. In our company there is a general manager, administrative manager, marketing manager, operational manager and financial manager. Each all of them will make sure themselves can carry out their roles as the best they can. In addition, we also choose the location at the town because our target market is the cat owners and from the T20 and M40 group. With our high-quality services and knowledgeable veterinary staff, we are confident that our clients will be happy with our offerings. The necessary care for pets that we will offer includes grooming, spa services and health care. We’ll also provide cats a place to live comfortably with a good hotel service and the veterinary cares and also provides essential supply products for cats. We hope that Neko Cat Hotel will getting known not just in Pasir Gudang but all over Malaysia and can franchise our business to other places